A new method for measuring dynamic change of tracer distribution using dynamic single photon emission tomography with a slip-ring rotational gamma camera - Miyazaki, Y; Hashimoto, M; Kinuya, S; Murata, Y; Inoue, H; Shiozaki, J; Takimoto, M; Yoshioka, K; Nakajima, K; Taki, J (Nuclear medicine communications, 2002)
The clinical applicability of dynamic single photon emission tomograpy (SPET) using a dual-head gamma camera equipped with a slip-ring rotational mechanism, referred to as serial SPET, was examined in the present investigation. Serial SPET enables the production of tomographic images for any arbitrary time frame from an arbitrary range of data to 360 degrees. In a pre-clinical evaluation, a correlation between radioactivity concentration and serial SPET counts was evaluated in a phantom with continuous changes in 99mTc concentration. A differential value was obtained from each pair of SPET images; moreover, moving average approximation processing was investigated with respect to the elimination of noise in the data. In 11 and one patient presenting with cerebrovascular disease and meningioma, respectively, changes in SPET counts were evaluated when 99mTc ethyl cysteinate dimer (99mTc-ECD) was continuously administered at a constant rate in the resting state. Furthermore, in six of 11 subjects with cerebrovascular disease, changes occurring in SPET counts were examined by using acetazolamide loading while continuously administering 99mTc-ECD at a constant rate. Consequently, serial SPET enabled the evaluation of changes in radioactivity concentration over time in both the phantom and preliminary clinical studies. Data analysis by differential processing utilizing moving average approximation processing enabled the detection of minor changes in radioactivity concentration. An increase of 15.1+/-5.4% was observed in SPET counts of the unaffected cerebral hemisphere with acetazolamide loading. The response of the affected hemisphere was less prominent. These findings suggest that serial SPET would be an effective technique for the pharmacokinetic analysis of radiopharmaceuticals.